2018
DOI: 10.1136/vr.104619
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas encountered by small animal veterinarians: characterisation, responses, consequences and beliefs regarding euthanasia

Abstract: Small animal veterinarians' opinions were investigated regarding the frequency and nature of ethical dilemmas encountered, beliefs regarding euthanasia and balancing client and animal interests, prevalence and value of ethics training and proposals to mitigate the stressful effects of ethical dilemmas. The majority (52 per cent) of 484 respondents in the USA indicated via an online survey experiencing an ethical dilemma regarding the interests of clients and those of their patients at least weekly. Scenarios i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 40 publications
7
92
0
4
Order By: Relevance
“…In addition, cost, disease type, ethical considerations, logistic-or owner-imposed constraints may favour empirical treatment. Our findings are consistent with a survey study by Kipperman et al ,27 who found that 60.5% of questioned US veterinarians resort to empirical treatment at least a few times a week, multiple times per day or once per day due to client financial limitations. Our findings are also consistent with research from Robinson et al , 9 who observed 3,196 primary care consultations with dogs, cats and rabbits.…”
Section: Limitationssupporting
confidence: 93%
“…In addition, cost, disease type, ethical considerations, logistic-or owner-imposed constraints may favour empirical treatment. Our findings are consistent with a survey study by Kipperman et al ,27 who found that 60.5% of questioned US veterinarians resort to empirical treatment at least a few times a week, multiple times per day or once per day due to client financial limitations. Our findings are also consistent with research from Robinson et al , 9 who observed 3,196 primary care consultations with dogs, cats and rabbits.…”
Section: Limitationssupporting
confidence: 93%
“…One of the fundamental questions facing veterinarians is whether their primary allegiance is to the animal or to the pet owner. In a recent study, only 20% of small-animal veterinarians indicated that other practitioners prioritize the patients’ interests, and only 50% of practitioners characterized their own behavior as prioritizing their patients [ 49 ]. One barrier discouraging the animal advocacy position is economic; the veterinarian is dependent on the pet owner who pays for the veterinary services [ 50 ].…”
Section: Ethical Concernsmentioning
confidence: 99%
“…A US study found that female students also experienced higher levels of depression and anxiety, lower levels of life satisfaction, and lower levels of general health compared to male students . Gender difference in stress levels is likely to be multifactorial and higher stress levels associated with female gender could be due to other confounding factors such as being more empathetic which can lead to greater emotional burden . A study of German veterinarians also reported that women were significantly more concerned with a good working atmosphere and family friendly arrangements (indicators of job satisfaction) compared to men .…”
Section: Discussionmentioning
confidence: 99%
“…Other difficult clinical decisions such as convenience euthanasia of a healthy animal and financial limitations of the client can cause great moral distress . Veterinarians reported that their training did not adequately prepare them to manage ethically challenging situations . As ethically challenging situations may lead to moral stress or moral distress, preparing veterinarians to navigate ethically challenging situations might be helpful.…”
Section: Discussionmentioning
confidence: 99%